Nurse Practitioners' Education, Awareness, and Therapeutic Approaches for the Management of Fibromyalgia. (September 2016) - Hughes, Linda; Adair, Jean; Feng, Feng; Maciejewski, Stephanie; Sharma, Harsha
Abstract : BACKGROUND: In the United States, fibromyalgia affects 2%–5% of the adult population, rendering it the most common chronic, widespread pain condition. The American College of Rheumatology has published diagnostic criteria for fibromyalgia, with the latest version in 2010. PURPOSE: The purpose of this study was to evaluate nurse practitioners' education and awareness of fibromyalgia and to evaluate nurse practitioners' practices for the management of fibromyalgia. METHODS: Sixty-six nurse practitioners voluntarily completed an online survey regarding their education, diagnosis, and treatment options for patients with fibromyalgia. RESULTS: The majority of participants reported that they always or occasionally had difficulty diagnosing fibromyalgia and worried about labeling their patients as having fibromyalgia. The most commonly used agents were nonsteroidal anti-inflammatory drugs (70%), serotonin norepinephrine reuptake inhibitors (61%), selective serotonin reuptake inhibitors (51%), and muscle relaxants (44%). Nondrug therapies included exercise (88%), cognitive behavior therapy (58%), and nutrition (56%). CONCLUSION: Further education is needed for nurse practitioners to increase confidence in diagnosing and managing fibromyalgia.